Instructional Constraints Faced by Learners with Muscular Dystrophy: A Case of Joytown Special Primary School, Thika, Kenya - Wang'ang'a, Annrose Wanjiku; Wamocho, Franciscah Irangi; Kioy, Paul (Journal of the American Academy of Special Education Professionals, 2015)
The purpose of this study was to investigate the instructional constraints facing learners with muscular dystrophy in Joy Town special primary school, Thika, Kenya. Descriptive design was used for this study. The target population were all the 20 learners suffering from muscular dystrophy from S.A Joy Town Special Primary School. The total target population was 84. Random sampling was used on learners suffering from muscular dystrophy. Purposive sampling was used on the head teacher, parents, teachers, teacher aides, housemothers and medical personnel. The researcher used an interview and an observation guide to collect data for comprehensive results. Piloting of the instruments was done at Dagoretti special school to establish validity and reliability of instruments. Content related validity was used as a measure to determine validity. The researcher used the Human Capital Theory. Descriptive statistics were used to analyze data. Results revealed that there were major instructional constraints faced by learners suffering from muscular dystrophy that included; slowness in completing learning tasks, mobility problems, problems in manipulating teaching learning materials, inability to hold a pen, lack of specialized facilities among others.